2019
DOI: 10.1093/intimm/dxz054
|View full text |Cite
|
Sign up to set email alerts
|

Broad and systemic immune-modulating capacity of plant-derived dsRNA

Abstract: Plant-derived endornavirus dsRNA enhances a variety of immune responses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…To investigate the effects of LGP2 on IFN-β induction upon stimulation by different RNA species, we used synthetic RNA poly(I:C), virus (EMCV) and BPEVdsRNA extracted from bell pepper ( 18 ) to stimulate MDA5. HEK293T cells were stimulated as described in (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effects of LGP2 on IFN-β induction upon stimulation by different RNA species, we used synthetic RNA poly(I:C), virus (EMCV) and BPEVdsRNA extracted from bell pepper ( 18 ) to stimulate MDA5. HEK293T cells were stimulated as described in (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the OsEV dsRNA treatment in mice suppressed replication of Influenza A virus at an early stages of infection. In another study using BPEV, Hajake et al (2019) reported melanoma-suppressive effects in mice after injecting them with BPEV dsRNA. Furthermore, they found that BPEV dsRNA acted as an effective vaccine adjuvant.…”
Section: Resultsmentioning
confidence: 99%